Voltammetric extraction of heparin and low-molecular-weight heparin across 1,2-dichloroethane/water interfaces - Jing, Ping (Langmuir : the ACS journal of surfaces and colloids, 2009)
Heparin and low-molecular-weight heparin are voltammetrically extracted across 1,2-dichloroethane/water interfaces for the detection of these highly sulfated polysaccharides widely used as anticoagulants/antithrombotics in many medical procedures. A new heparin ionophore, 1-[4-(dioctadecylcarbamoyl)butyl]guanidinium, is the first to enable the voltammetric extraction of various polyanionic heparins with average molecular weights of up to approximately 20 kDa including those in commercial preparations (i.e., Arixtra (1.5 kDa), Lovenox (4.5 kDa), and unfractionated heparin (15 kDa), as well as chromatographically fractionated heparins (7, 9, 15, and 20 kDa)). Facilitated Arixtra extraction is fully and quantitatively characterized by micropipet voltammetry to propose that cooperative effects from strong heparin-binding capability and high lipophilicity of this ionophore are required for the formation of an electrically neutral and highly lipophilic complex of a heparin molecule with multiple ionophore molecules to be extracted into the nonpolar organic phase. At the same time, the participation of multiple ionophore molecules in interfacial complexation with a heparin molecule slows down its extraction across the interface. This kinetic limitation is enhanced by fast mass transfer at a micropipet-supported interface to compromise thermodynamically favorable selectivity for heparin and an important contaminant, oversulfated chondroitin sulfate, thereby requiring a macroscopic interface for sensing applications. Another highly lipophilic guanidinium ionophore, N,N-dioctadecylguanidinium, cannot completely extract even Arixtra, which indicates the importance of elaborate ionophore design for heparin extraction